2012
DOI: 10.1093/nar/gks882
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic characterization of the reaction pathway of box H/ACA RNA-guided pseudouridine formation

Abstract: The box H/ACA RNA-guided pseudouridine synthase is a complicated ribonucleoprotein enzyme that recruits substrate via both the guide RNA and the catalytic subunit Cbf5. Structural studies have revealed multiple conformations of the enzyme, but a quantitative description of the reaction pathway is still lacking. Using fluorescence correlation spectroscopy, we here measured the equilibrium dissociation constants and kinetic association and dissociation rates of substrate and product complexes mimicking various r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 30 publications
(49 reference statements)
7
43
0
Order By: Relevance
“…55 The snoRNA (called sRNA in Archaea) acts as guide for the protein components with Nop10 and the C synthase NAP57 (higher eukaryotes) or Cbf5 (yeast, Archaea) as minimal requirements. 56,57 Non-essential components Gar1 and L7Ae (or Nhp2 in Eukarya) are involved in catalysis and product release 58 or in substrate binding by interaction with Nop10 [59][60][61] , respectively. Cbf5 is also capable of guide RNA free catalysis, the activity of which is increased by Gar1 and Nop10.…”
Section: Enzymatic Formation Of C Residuesmentioning
confidence: 99%
“…55 The snoRNA (called sRNA in Archaea) acts as guide for the protein components with Nop10 and the C synthase NAP57 (higher eukaryotes) or Cbf5 (yeast, Archaea) as minimal requirements. 56,57 Non-essential components Gar1 and L7Ae (or Nhp2 in Eukarya) are involved in catalysis and product release 58 or in substrate binding by interaction with Nop10 [59][60][61] , respectively. Cbf5 is also capable of guide RNA free catalysis, the activity of which is increased by Gar1 and Nop10.…”
Section: Enzymatic Formation Of C Residuesmentioning
confidence: 99%
“…Gar1 was found to make additional interactions with the Cbf5 b7b10 loop, inducing the enzyme to adopt an open state which facilitates substrate loading and product release [27,33]. Formation of the substrate-bound complex changes the positioning of the thumb as it contacts the substrate RNA, and thus this conformation represents the closed state of the enzyme [27,33].…”
Section: Introductionmentioning
confidence: 99%
“…Gar1 was found to make additional interactions with the Cbf5 b7b10 loop, inducing the enzyme to adopt an open state which facilitates substrate loading and product release [27,33]. Formation of the substrate-bound complex changes the positioning of the thumb as it contacts the substrate RNA, and thus this conformation represents the closed state of the enzyme [27,33]. Biochemical studies based on the in vitro reconstitution of catalytically active particles showed that Gar1 is not required for complete modification of an excess of substrate RNAs in singleturnover reactions [17], but its presence influences substrate placement [34] and enhances the rate of J formation [17,35].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations